The problem of knowledge between determinism and indeterminism ( Pierre Laplace as a Model ) - حسن محمود; إبراهيم رزوق (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
There are many epistemological concepts that divide the world of knowledge into two contradictory knowledge doctrines , So that the world of knowledge is governed by the law of dualism that governs the entire universe , Every being in the world of existence has an existential opposite , There are many contradictory existential dualities in the world of existence , such as: existence and nothingness, end and infinity, light and darkness, order and chaos , evolution and inertia, affirmation and negation, Likewise, there are many contradictory epistemological binaries in the world of knowledge, among them: objectivity and subjectivity, meaning and non-meaning , absolute and relative, determinism and indeterminism , and The epistemological relationship between the concepts of determinism and indeterminism represented one of the most important problems in knowledge , Where the philosophers of science divided into two parts , Someone believes that the principle of determinism is the prevailing epistemological principle in the world of knowledge , And that all scientific facts in the world of knowledge are governed by the principle of improvement , The French astronomer, mathematician, and philosopher of science: Pierre Laplace is one of the most prominent founders of the doctrine of determinism , While the other section believes that the principle of indeterminism is the dominant epistemological principle in the world of knowledge , And that all cognitive processes, epistemological theories and scientific phenomena are governed by the principle of indeterminism , Accordingly, a dialectical relationship emerged between the concepts of determinism and indeterminism, Where a section of the philosophers of science considered that knowledge is inevitable in its essence, All knowledge is formed according to determinism, regular laws , The presence of certain scientific conditions within the world of knowledge will inevitably lead to the emergence of certain scientific results , And every field of knowledge has its own scientific laws that are not suitable for other scientific and cognitive fields , While the other section of the philosophers of science considered that knowledge is not deterministic in its essence , Where they decide that knowledge proceeds indeterminism , knowledge is formed irregularly and laws of knowledge are formed according to different conditions , The same cognitive conditions produce different cognitive results , Based on that, knowledge develops in an indeterminism way, and according to various scientific variables, it directly contributes to creating a knowledge environment of knowledge that is not bound by certain determinism conditions , Rather, it creates constantly renewed cognitive conditions that fit its own cognitive structure, Within this epistemological context, both deterministic epistemology and indeterministic theory contributed to the development of the field of epistemology through a set of epistemological principles formulated by philosophers of science in all fields of knowledge and science .